Film in the Workplace: Exploring the Film Holdings of the Marks and Spencer Company Archive. Issue 4 (September 2022) - Shail, Robert
Abstract : This article explores the possibilities offered to researchers by the film holdings which can be found in archives that exist outside of the more conventional, subject-specific film archives in the UK such as those held by the British Film Institute. The Marks and Spencer Company Archive exists principally to hold the company records and related materials illustrating the history of one of the UK's most successful and long-established high-street retailers. Although their film holdings are extensive, these materials are somewhat tangential to the main collection and might not be a source that has been recognised to date by film scholars. Such collections also exist in a number of other commercial organisations, as well as public sector ones. The article details the holdings, arranging them into significant groupings, and analyses their style and content with particular attention to their potential status as both history on film and as film form. In doing so, it posits the opportunity to consider further exploration of film holdings normally thought of as outside film scholarship, and the value of more utilitarian forms of film-making than those usually found in entertainment or art cinema.